Placental Underperfusion in a Rat Model of Intrauterine Growth Restriction Induced by a Reduced Plasma Volume Expansion - Bibeau, Karine (PLoS One, 2016)
Lower maternal plasma volume expansion was found in idiopathic intrauterine growth restriction (IUGR) but the link remains to be elucidated. An animal model of IUGR was developed by giving a low-sodium diet to rats over the last week of gestation. This treatment prevents full expansion of maternal circulating volume and the increase in uterine artery diameter, leading to reduced placental weight compared to normal gestation. We aimed to verify whether this is associated with reduced remodeling of uteroplacental circulation and placental hypoxia. Dams were divided into two groups: IUGR group and normal-fed controls. Blood velocity waveforms in the main uterine artery were obtained by Doppler sonography on days 14, 18 and 21 of pregnancy. On day 22 (term = 23 days), rats were sacrificed and placentas and uterine radial arteries were collected. Diameter and myogenic response of uterine arteries supplying placentas were determined while expression of hypoxia-modulated genes (HIF-1α, VEGFA and VEGFR2), apoptotic enzyme (Caspase -3 and -9) and glycogen cells clusters were measured in control and IUGR term-placentas. In the IUGR group, impaired blood velocity in the main uterine artery along with increased resistance index was observed without alteration in umbilical artery blood velocity. Radial uterine artery diameter was reduced while myogenic response was increased. IUGR placentas displayed increased expression of hypoxia markers without change in the caspases and increased glycogen cells in the junctional zone. The present data suggest that reduced placental and fetal growth in our IUGR model may be mediated, in part, through reduced maternal uteroplacental blood flow and increased placental hypoxia.